Needs Analysis for Developing Project-Based Learning E-Modules on the Human Respiratory System for Class XI Phase F Students - Sukatni Sukatni; Puguh Karyanto; Baskoro Adi Prayitno (FKIP - Universitas Riau, 2026)
This study aims to analyze the need for developing a Project-Based Learning (PjBL)-based e-module on the human respiratory system to strengthen senior high school students’ critical thinking skills. The needs analysis was carried out through questionnaires distributed to students and biology teachers. Findings reveal that students frequently encounter difficulties in understanding respiratory system concepts when learning is limited to verbal explanations or textbook-based materials. Students also expressed a preference for digital learning resources equipped with visual representations, videos, practical tasks, and clearly structured learning stages. Biology teachers emphasized the urgency of providing digital media aligned with the Merdeka Curriculum that support collaborative activities and the development of higher-order thinking skills. They also agreed that a PjBL-based e-module has the potential to enhance students’ motivation, engagement, and conceptual understanding of the respiratory system. Therefore, the development of a PjBL-based e-module is considered necessary as an interactive and effective learning medium that accommodates both student and teacher needs while promoting meaningful learning and critical thinking.